Decreased T-Cell Programmed Death Receptor-1 Expression in Pregnancy-Associated Melanoma. (March 2019) - Ko, Jennifer S.; Gastman, Brian R.; Conic, Ruzica; Tellez Diaz Trujillo, Alejandra; Diaz-Montero, Claudia Marcela; Billings, Steven D.; Tarhini, Ahmad; Funchain, Pauline; Atanaskova Mesinkovska, Natasha
Abstract : Introduction: Pregnancy depends on tolerance of an immunologically foreign fetus through type 1 T-cell suppression. Worse melanoma outcomes have been described within 1 year of childbirth. We assessed immunopathologic factors that may account for the observed negative impact of pregnancy on outcome. Materials and Methods: Women of child-bearing age with ≥24 months follow-up were identified from our Institutional Melanoma Registry. Women with available primary tumor blocks were compared [history of childbirth within 1 year of diagnosis (CB1Y) (n = 18) vs. nonpregnant age-matched controls (n = 13)]. Immunohistochemical staining with quantification of immune infiltrates: CD68 + tumor-associated macrophages, CD3 + tumor-infiltrating T cells, and PD-1 + activated/exhausted T cells; and hematolymphangiogenesis: CD31 + /D2-40 − blood vessels and D2-40 + lymphatics was performed by 2 blinded dermatopathologists. Results: CB1Y tumors showed decreased CD3 + tumor-infiltrating T cells ( P < 0.05) with significantly reduced PD1 expression ( P ⩽ 0.05). The CD3:PD1 ratio was higher in CB1Y ( P < 0.05). Other tested parameters did not significantly differ between the 2 groups. Discussion: As PD1 expression is induced during type 1 T-cell activation, these data suggest that immune ignorance or suppression may predominate in CB1Y. Further studies are required to identify interventions that may promote tumor-associated T-cell inflammation in such patients.